Positive Pressure Bronchoscopy Technique: Case Report. (February 2016) - Hall, Michael B.; Johnston, Douglas R.; Barth, Patrick
Objective: Foreign body aspiration into the tracheobronchial tree continues to be a challenging problem for otolaryngologists. This is especially true in patients with poor pulmonary reserve. Methods: We describe a novel technique in which an endotracheal sheathed bronchoscope is used as a means to provide positive pressure ventilation simultaneously during foreign body extraction. Results: This new technique afforded the bronchoscopist more time during retrieval of the foreign body where previous attempts were limited by rapid desaturations and the overall nature of the foreign body. Conclusion: The endotracheal sheathed bronchoscope is a safe and efficacious technique for challenging airway foreign bodies complicated by a patient's limited pulmonary reserve.